Beginning Visual CSharp 2005 Express Edition - Wright, Peter (Apress, 2012)
It was in Amsterdam, in 2004, that I first discovered the Express tools from Microsoft. During the keynote at Microsoft’s huge developer event, TechEd, various personas from inside the company were getting extremely animated about the possibilities these tools gave to the development community. At a time when most of us thought Microsoft was quietly beavering away on Visual Studio 2005 and nothing else, the boys and girls from Redmond did a massive turnabout and announced that they would be, at last, introducing a set of extremely well-priced reduced-functionality development tools aimed specifically at students and hobbyists. I saw something different, though. With a very cheap price (they’re actually free at the time of this printing), the Express tools are the ideal way for anyone to get up to speed in .NET development. Ignoring the obvious benefits these tools have for students, there’s a whole raft of people out there coding like demons in Java, classic Visual Basic, and even the Linux tools that prior to the release of the Express family may never have had a chance to experience the power and versatility of .NET. I sat down at lunch to discuss the book ideas with Gary Cornell, Apress’s venerable publisher, and something else occurred to me. The Express family of tools probably represents the most groundbreaking move in development tools Microsoft has made since the release of Visual Basic way back in the early 90s. Visual Basic opened up a previously locked world, enabling practically anyone to sit down and write computer programs that would run on the Windows operating system. It was a paradigm shift away from the traditional crusty world of C++ compilers, huge technical reference books, and headaches, and into a world where developing a program was as simple as dragging and dropping components with a mouse and then gluing them all together with code.